Time-resolved crystallography and protein design: signalling photoreceptors and optogenetics - Moffat, Keith (The Royal Society, 2014)
Time-resolved X-ray crystallography and solution scattering have been successfully conducted on proteins on time-scales down to around 100 ps, set by the duration of the hard X-ray pulses emitted by synchrotron sources. The advent of hard X-ray free-electron lasers (FELs), which emit extremely intense, very brief, coherent X-ray pulses, opens the exciting possibility of time-resolved experiments with femtosecond time resolution on macromolecular structure, in both single crystals and solution. The X-ray pulses emitted by an FEL differ greatly in many properties from those emitted by a synchrotron, in ways that at first glance make time-resolved measurements of X-ray scattering with the required accuracy extremely challenging. This opens up several questions which I consider in this brief overview. Are there likely to be chemically and biologically interesting structural changes to be revealed on the femtosecond time-scale? How shall time-resolved experiments best be designed and conducted to exploit the properties of FELs and overcome challenges that they pose? To date, fast time-resolved reactions have been initiated by a brief laser pulse, which obviously requires that the system under study be light-sensitive. Although this is true for proteins of the visual system and for signalling photoreceptors, it is not naturally the case for most interesting biological systems. To generate more biological targets for time-resolved study, can this limitation be overcome by optogenetic, chemical or other means?